2015
DOI: 10.1021/acs.jpclett.5b01739
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin to Lipid Raft-Endocytosis via Controlled Surface Chemistry and Efficient Perinuclear Targeting of Nanoparticle

Abstract: Nanoparticle interacts with live cells depending on their surface chemistry, enters into cell via endocytosis, and is commonly trafficked to an endosome/lysozome that restricts subcellular targeting options. Here we show that nanoparticle surface chemistry can be tuned to alter their cell uptake mechanism and subcellular trafficking. Quantum dot based nanoprobes of 20-30 nm hydrodynamic diameters have been synthesized with tunable surface charge (between +15 mV to -25 mV) and lipophilicity to influence their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 69 publications
4
98
0
Order By: Relevance
“…The ζ-potential of quantum dots has been suggested to dictate their route of entry into cells. 55 It has been shown that quantum dots with lower surface potentials (corresponding to ζ-potential between −10 and +10 mV), similar to those used in this work (apparent ζ-potential of −4 ± 1 mV in cell culture media), tend to enter the cell via lipid raft-mediated endocytosis. 55 While the Qdots used in this study caused no discernable decrease in cell viability (Fig.…”
Section: Primary Amine-terminated Qdots Preferentially Co-localize Wimentioning
confidence: 51%
See 2 more Smart Citations
“…The ζ-potential of quantum dots has been suggested to dictate their route of entry into cells. 55 It has been shown that quantum dots with lower surface potentials (corresponding to ζ-potential between −10 and +10 mV), similar to those used in this work (apparent ζ-potential of −4 ± 1 mV in cell culture media), tend to enter the cell via lipid raft-mediated endocytosis. 55 While the Qdots used in this study caused no discernable decrease in cell viability (Fig.…”
Section: Primary Amine-terminated Qdots Preferentially Co-localize Wimentioning
confidence: 51%
“…55 It has been shown that quantum dots with lower surface potentials (corresponding to ζ-potential between −10 and +10 mV), similar to those used in this work (apparent ζ-potential of −4 ± 1 mV in cell culture media), tend to enter the cell via lipid raft-mediated endocytosis. 55 While the Qdots used in this study caused no discernable decrease in cell viability (Fig. S1 †), it has been shown that NPs can induce significant changes in cell function, such as changes in gene expression, even without detectable changes in cell viability.…”
Section: Primary Amine-terminated Qdots Preferentially Co-localize Wimentioning
confidence: 51%
See 1 more Smart Citation
“…An upper size limit reported for particles entering via this pathway is 200 nm [8, 11]. Silica NPs of 200 nm and polymeric NPs of 100–200 nm were reported to internalize predominantly through CME [11, 28], and the positive charge on the surface of quantum dots [29], dendrimers [30] and polymer NPs [10, 31] was shown to increase the probability of internalization via CME rather than the use of other endocytic pathway. In our study, the inhibitors of CME were not very successful to inhibit the uptake of Rubipy-SiO 2 NPs by CaCo-2 cells; however the effect of chlorpromazine and the colocalisation with clathrin suggests a minor role of this pathway in the internalization of 30 nm Rubipy-SiO 2 NPs.…”
Section: Discussionmentioning
confidence: 99%
“…In general, particles of 50–80 nm are endocytosed through caveolae-mediated endocytosis [43,44,45]; particles <150 nm in diameter are taken up via classic receptor-mediated endocytosis through clathrin-coated pits [45,46]; and larger particles (>500 nm) are endocytosed via macropinocytosis and phagocytosis and restricted to professional antigen presenting cells (APC), such as macrophages and immature DCs [38]. Particles can also be endocytosed via clathrin- and caveolae-independent lipid raft-mediated mechanisms, but the size-restrictions are not well understood [44,46]. Upon internalization, the particles are hydrolyzed in the endosome/lysosomes of APCs, and antigens are then processed and complexed with MHC class II molecules for subsequent presentation and activation of CD4 T cells [47,48].…”
Section: The Effect Of Antigen Presenting Cellsmentioning
confidence: 99%